The Composition Matters : Capital Inflows and Liquidity Crunch During a Global Economic Crisis - Tong, Hui.; Wei, Shang-Jin. (Washington, D.C. : International Monetary Fund, 2009)
We study whether capital flows affect the degree of credit crunch faced by a country's manufacturing firms during the 2007-09 crisis. Examining 3823 firms in 24 emerging countries, we find that the decline in stock prices was more severe for firms that are intrinsically more dependent on external finance for working capital. The volume of capital flows has no significant effect on the severity of the credit crunch. However, the composition of capital flows matters: pre-crisis exposure to non-FDI capital inflows worsens the credit crunch, while exposure to FDI alleviates the liquidity constraint. Similar results also hold surrounding the Lehman Brothers bankruptcy.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet